Disposition of cannabinoids and their metabolites in serum, oral fluid, sweat patch and urine from healthy individuals treated with pharmaceutical preparations of medical cannabis. (6th November 2020) - Pérez‐Acevedo, Ana P.; Pacifici, Roberta; Mannocchi, Giulio; Gottardi, Massimo; Poyatos, Lourdes; Papaseit, Esther; Pérez‐Mañá, Clara; Martin, Soraya; Busardò, Francesco P.; Pichini, Simona; Farré, Magí
Abstract : Recently, several countries authorized the use of cannabis flowering tops (dried inflorescences) with a standardized amount of Δ9‐tetrahydrocannabinol (THC), cannabidiol (CBD) and their acidic precursors [Δ‐9‐tetrahydrocannabinolic acid A (THCA‐A) and cannabidiolic acid (CBDA)] to treat neurogenic pain. We studied the acute pharmacological effects and disposition of cannabinoids and their metabolites in serum, oral fluid, sweat patch and urine of 13 healthy individuals treated with medical cannabis decoction and oil. Cannabinoids and their metabolites were quantified by ultrahigh performance tandem mass spectrometry. Even if the oil contained a significantly higher amount of THC, the absorption of THC and its metabolites were similar in both herbal preparations. Conversely, whereas oil contained a significantly higher amount of CBD and a lower amount of CBDA, absorption was significantly higher after decoction intake. Only cannabinoids present in both herbal preparations (THC, CBD, THCA‐A and CBDA) were found in oral fluid, due to the higher acidity compared with that of serum. THC metabolites urinary excretion was always higher after decoction administration. Decoction induced greater feeling of hunger and drowsiness than oil preparation. Pharmacokinetics of cannabinoids, their precursors and their metabolites in biological fluids of individuals treated with cannabis decoction and oil showed a high interindividual variability. The aqueous preparation was generally better absorbed than the oil, even if it contained a minor amount of THC, THCA‐A and CBD.